2022
DOI: 10.7554/elife.76941
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the tolerance of the genetic code to altered codon size

Abstract: Translation using four-base codons occurs in both natural and synthetic systems. What constraints contributed to the universal adoption of a triplet-codon, rather than quadruplet-codon, genetic code? Here, we investigate the tolerance of the Escherichia coli genetic code to tRNA mutations that increase codon size. We found that tRNAs from all twenty canonical isoacceptor classes can be converted to functional quadruplet tRNAs (qtRNAs). Many of these selectively incorporate a single amino acid in response to a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…As a proof of concept, we used the quadruplet tRNA qtRNA Gly CCCC , as it can be easily aminoacylated by GlyRS 41,42 and is known to be one of the most efficient qtRNAs. 43 mRNA 7 was designed such that the fulllength peptide containing the FLAG tag is translated only when a qtRNA reads the quad codon as GGGG (Figure 5a). However, the template also contains a N-terminal His6 tag to track the yields and products of triplet codon readthrough either by near-cognate tRNAs or by qtRNA Gly CCCC itself.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a proof of concept, we used the quadruplet tRNA qtRNA Gly CCCC , as it can be easily aminoacylated by GlyRS 41,42 and is known to be one of the most efficient qtRNAs. 43 mRNA 7 was designed such that the fulllength peptide containing the FLAG tag is translated only when a qtRNA reads the quad codon as GGGG (Figure 5a). However, the template also contains a N-terminal His6 tag to track the yields and products of triplet codon readthrough either by near-cognate tRNAs or by qtRNA Gly CCCC itself.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Since the mS12 ribosomes demonstrate an enhanced ability to resist near-cognate readthrough, we were curious to see to what extent they could improve quadruplet codon reading by quadruplet tRNAs. As a proof of concept, we used the quadruplet tRNA qtRNA Gly CCCC , as it can be easily aminoacylated by GlyRS , and is known to be one of the most efficient qtRNAs . mRNA 7 was designed such that the full-length peptide containing the FLAG tag is translated only when a qtRNA reads the quad codon as GGGG (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…DeBenedictis et al, (2022) reported the translation of four-base codons in natural and synthetic systems 25 . They reported 20 isoacceptors can be changed to functional quadruplet tRNAs 25 . Anderson et al .…”
Section: Discussionmentioning
confidence: 99%
“…Although the origin of the genetic code has been studied for decades [6] [7] [8] [9] [10] [11] [12], the origin of the triplet nature of the genetic code has been seldom mentioned in the literature. The triplet codons was suggested to expand from doublet codons [13] [14] [15] [16] or to reduce from longer non-triplet codons [17]; it was argued that the triplet nature was forced by translocation processes with the help of fluctuations when a Brownian regime molecular machine drives the chain along the polymer in steps of three monomers [18] [19] [20]; syntheses of 4-base decoding tRNAs with improved efficiency suggested that the triplet codon code was selected because it is simpler and sufficient, not because a quadruplet codon code is unachievable [21] [22]. The theories to explain the triplet nature of the genetic code are quite different in the literature, which may weaken each other.…”
Section: Introductionmentioning
confidence: 99%